Youth and socialization: violence as a social fact - Sebastião, João (13th Conference of the European Sociological Association, 2017)
Youth and socialization: violence as a social fact This communication focuses on the critical analysis of some of the main concepts in use in the analysis of situations of violence among youth, such as bullying, questioning their use in the sociological field. Analyzing sociologically youth violence implies to build a problematic capable of taking in account of the multidimensionality of the phenomenon, questioning the conceptions that see it as the simple result of poorly socialized children or behavioral disorders. We will argue that the recurrent use of such concepts without due sociological questioning has led to the diffusion of individualistic and psychologistic explanations of violent behaviors, devaluing or ignoring even the cultural, social and interactive frameworks in which they occur. Based on the sociological debate on violence, namely the contributions of Norbert Elias and Randall Collins, and the results of several researches about situations of violence among young people in different contexts of interaction (in school, dating), we will present a theoretical model that allows the adoption of a definition of violence capable of considering not only the act itself, but also the relational framework in which it takes place.